2023
DOI: 10.1111/odi.14683
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periodontal diseases affect the leukocyte profiles of umbilical cord blood: A cohort study

Abstract: AimThis study evaluated the connection of periodontal status with the leukocyte profiles of maternal peripheral blood (MPB) and umbilical cord blood (UCB).Materials and MethodsNinety‐nine pregnant females were recruited, and their data were collected via questionnaire and from medical records, including demographics, systemic conditions, complete blood count (CBC) and C‐reaction protein (CRP) level in MPB. Full‐mouth periodontal assessment was performed. CBC and CRP levels in UCB were measured after parturitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In addition, it has also been documented that periodontal status is significantly related to fetal growth parameters, suggesting the fact that existing periodontal inflammation contributes to fetal growth restriction [48,49]. As such, in addition to the commonly used periodontal parameters, the emerging variable so called PISA has been measured for quantifying the burden of periodontal inflammation in the present study [32,33]. Interestingly, the PISA shows a significantly positive correlation with the risk of SGA.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, it has also been documented that periodontal status is significantly related to fetal growth parameters, suggesting the fact that existing periodontal inflammation contributes to fetal growth restriction [48,49]. As such, in addition to the commonly used periodontal parameters, the emerging variable so called PISA has been measured for quantifying the burden of periodontal inflammation in the present study [32,33]. Interestingly, the PISA shows a significantly positive correlation with the risk of SGA.…”
Section: Discussionmentioning
confidence: 62%
“…Yet, the public is not fully aware of oral/periodontal health, and the mothers-to-be often could not get access to adequate oral care on a regular basis [52]. Our recent work on the considerable link between maternal periodontal diseases and systemic disorders further highlights the profound importance of integrating oral healthcare into professional maternal schemes for the optimal health and well-being of pregnant females and their newborn babies [32,53]. Since periodontal diseases are a modifiable risk factor of neonatal adverse outcomes, it is strongly suggested that both oral healthcare professionals and obstetricians should raise their awareness of periodontal health in child-bearing women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation